2003
DOI: 10.1002/chem.200204584
|View full text |Cite
|
Sign up to set email alerts
|

Alkyne Migration in Alkylidene Carbenoid Species: A New Method of Polyyne Synthesis

Abstract: The synthesis of conjugated polyyne structures via a modification of the Fritsch-Buttenberg-Wiechell (FBW) rearrangement is reported. Our adaptation provides for the 1,2-migration of an alkyne in a carbene/carbenoid intermediate that is conveniently effected via lithium-halogen exchange with the appropriate dibromo-olefinic precursor. This rearrangement is quite rapidly accomplished under mild conditions (hexane solution, -78 degrees C), and the seemingly high migratory aptitude of the alkynyl moiety provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 79 publications
(35 reference statements)
1
69
1
1
Order By: Relevance
“…36,37 At first, alkyne 10 was converted to ynone 32 in two steps (Scheme 7, route A). Lithiation of 10 followed by a reaction with paraformaldehyde resulted in alcohol 33, which was subsequently oxidized to ynone 32 by Swern oxidation.…”
Section: Scheme 2 Synthesis Of 19 and 20mentioning
confidence: 99%
“…36,37 At first, alkyne 10 was converted to ynone 32 in two steps (Scheme 7, route A). Lithiation of 10 followed by a reaction with paraformaldehyde resulted in alcohol 33, which was subsequently oxidized to ynone 32 by Swern oxidation.…”
Section: Scheme 2 Synthesis Of 19 and 20mentioning
confidence: 99%
“…Fortunately, Tykwinski et al have demonstrated that the migratory aptitude of alkynes in FWB rearrangements is poor in coordinating solvents. 23 We therefore concluded that any FWB rearrangement would most likely involve migration of the aryl group and we prepared three substrates to examine any putative rearrangements occurring. By altering the electron demand of the aryl substituent we hoped to gain some insight as to whether a 1,2-rearrangement was competing with enediyne formation.…”
Section: Scheme 5 Potential Exchange Reactionsmentioning
confidence: 99%
“…Apart from dendrimer end-capped oligoynes, which mainly help to stabilize the system, many different functional end-groups have been incorporated into the two ends of sp carbon chains by chemists in order to study the electronic properties and explore possible applications of this class of compounds (Scheme 10.2) [10,[40][41][42][43]. The electronic structures of organic polyynyl chains with various end-groups have been studied by Bohlmann [35,36], Walton [44,45], Hirsch [12,13,39], and Tykwinski [46,47]. The electronic absorption spectra of the polyynes generally show highly structured absorption bands, with the lowest energy absorption bands showing a bathochromic shift with increasing number of CcC units.…”
Section: Organic Polyynesmentioning
confidence: 99%
“…In addition to the one-dimensional wire-like compounds, a considerable number of two-dimensional and three-dimensional architectures have also been built, using the chemistry of the alkynyl units in an elegant manner, by the groups of Bunz [54], Diederich [55][56][57], de Meijere [58], Moore [59], Tykwinski [46,47], Haley [60], Vollhardt [22][23][24][25][26][27] and others [61,62]. In particular, a series of perylene-terminated phenylene ethynylene dendrimers with energy gradients was successfully synthesized and isolated by Moore and coworkers (Scheme 10.5) [63]; the luminescence and energy transfer properties have been evaluated.…”
Section: Organic Polyynesmentioning
confidence: 99%